2019
DOI: 10.1037/hea0000800
|View full text |Cite
|
Sign up to set email alerts
|

Associations between self-monitoring and weight change in behavioral weight loss interventions.

Abstract: Objective:The current study is a secondary analysis of the Live SMART trial, a randomized controlled trial comparing a behavioral weight loss (BWL) condition delivered via smartphone (SMART) to a group-based BWL condition (GROUP) and a control condition (CONTROL). Given the established importance of self-monitoring for weight loss, the aims were to evaluate bidirectional associations between adherence to self-monitoring and weight change and to examine the moderating effect of treatment condition on these asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…In support of this, adherence to the self-regulation steps in the intervention arm was still associated with weight loss success. We found that adherence to selfweighing was a significant predictor of weight loss success in the control arm too, and this matches other observational data (Goldstein et al, 2019;LaRose, Lanoye, Tate, & Wing, 2016;Van Wormer, French, Pereira, & Welsh, 2008). Adherence to self-weighing may reflect persistence in weight loss efforts.…”
Section: Self-regulation Is Effective For Weight Losssupporting
confidence: 88%
“…In support of this, adherence to the self-regulation steps in the intervention arm was still associated with weight loss success. We found that adherence to selfweighing was a significant predictor of weight loss success in the control arm too, and this matches other observational data (Goldstein et al, 2019;LaRose, Lanoye, Tate, & Wing, 2016;Van Wormer, French, Pereira, & Welsh, 2008). Adherence to self-weighing may reflect persistence in weight loss efforts.…”
Section: Self-regulation Is Effective For Weight Losssupporting
confidence: 88%
“…We identified 4,248 records in our database and hand searches. After the deduplication and screening stages, 53 papers describing 39 unique RCTs met all inclusion criteria (32‐84).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies assessed weight outcomes at follow‐up visits ranging from 3 to 12 months after the end of the intervention (46,50,57,59,62,73,74,77). Of the 39 trials, 20 trials had two treatment arms (34,41,42,45,46,53,57,60,70,74,76‐78,80‐84), 15 trials had three arms (35,40,44,49,50,52,54,55,59,62,66,69,73,79), 3 trials had four arms (32,33,71), and 1 trial had five arms (48). In total, there were 67 arms with digital self‐monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…Nominal groups were presented six scenarios for voting and discussion. These scenarios were written by the research team using a taxonomy of five domains of placebogenic techniques22–26 derived from experimental and clinical studies27 to create six theoretically plausible placebogenic scenarios for primary care (table 2). Techniques from the five domains22 were used to create the scenarios: (1) The patient’s beliefs and characteristics informed ‘Withholding side effects’, (2) The healthcare setting informed ‘Monitoring’, (3) The practitioner’s beliefs and characteristics informed ‘GP endorsement’, (4) The patient-practitioner interaction informed ‘Idealised consultation’ and (5) Treatment characteristics informed ‘Deceptive’/‘Open-label placebo pills’.…”
Section: Methodsmentioning
confidence: 99%